Fabrication of Large-Grain Thick Polycrystalline Silicon Thin Films via Aluminum-Induced Crystallization for Application in Solar Cells - Hsiao-Yeh Chu; Min-Hang Weng; Chen Lin (International Journal of Photoenergy)
The fabrication of large-grain 1.25 μm thick polycrystalline silicon (poly-Si) films via two-stage aluminum-induced crystallization (AIC) for application in thin-film solar cells is reported. The induced 250 nm thick poly-Si film in the first stage is used as the seed layer for the crystallization of a 1 μm thick amorphous silicon (a-Si) film in the second stage. The annealing temperatures in the two stages are both 500°C. The effect of annealing time (15, 30, 60, and 120 minutes) in the second stage on the crystallization of a-Si film is investigated using X-ray diffraction (XRD), scanning electron microscopy, and Raman spectroscopy. XRD and Raman results confirm that the induced poly-Si films are induced by the proposed process.